Analisis Hasil Pengujian California Bearing Ratio Penambahan Slag Nikel Pada Tanah Lempung - Patrick Setiawan Linga; Irwan Lie Keng Wong; Eltrit Bima Fitrian (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Soil improvement on clay soils needs to be done because clay soils have a large water content, large pore numbers, large index plasticity, small volume weight, causing the carrying capacity of clay soils to be low. This study is intended to determine the analysis of the test results of the California Bearing Ratio of nickel slag additions on clay soils. The methodology in this research is to carry out various tests of soil characteristics after which planning the composition of the mixture, obtaining the optimum moisture content value from the Compaction test obtaining the soil carrying capacity value from the California Bearing Ratio (Unsoaked Design CBR) test. In the research conducted at the Soil Mechanics Laboratory, Faculty of Engineering, Department of Civil Engineering, Christian University of Indonesia Paulus Makassar, the results obtained showed the characteristics of the soil tested to meet as clay. In the compaction test at point 1 and point 2 using a mixture of variations of 0%, 20%, 25%, 30%, 35% experienced an increase in optimum moisture content and maximum dry density. At point 1, the increase in dry density in testing nickel slag content from 0% as much as 1,098 continued to increase in the addition of nickel slag up to 30% as much as 1,123 continued to increase in the addition of nickel slag levels up to 35% as much as 1,214. In the CBR test, namely CBR without immersion, there was an increase in the CBR value at point 1 or at point 2 where the CBR value at point 1 was 1.97%, 2.63%, 3.80%, 5.70%, 6.33% while the CBR value at point 2 was 2.24%, 2.60%, 3.23%, 3.97%, 5.17%. From the results of the study, it can be concluded that nickel slag can be used to increase the carrying capacity of clay soils because nickel slag can increase the CBR value of the soil.